2008
DOI: 10.1002/mds.22199
|View full text |Cite
|
Sign up to set email alerts
|

Poor dopaminergic response of impaired dexterity in Parkinson's disease: Bradykinesia or limb kinetic apraxia?

Abstract: Patients with Parkinson's disease (PD) often show impaired manual dexterity even when being only minimally bradykinetic, suggesting that they may have limb kinetic apraxia (LKA), that is, a loss of fine motor skill not explained by elemental motor deficits. To explore this dissociation, we investigated the differential dopaminergic responsiveness of dexterity and bradykinesia in PD. Twelve patients with PD (4 women, age 64.4 +/- 8.3, mean + SD) and 12 matched healthy controls (64.8 +/- 8.9) were tested twice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 30 publications
5
62
0
2
Order By: Relevance
“…Validity of AST in atypical parkinsonism remains to be established. In addition, the contribution of apraxia to poorer ADL performance in PD, as demonstrated herein and in earlier reports [6,9,10], might have consequences for occupational and physical therapy. For instance, integration of strategy training in non-demented PD, shown to be effective in apraxic stroke patients [22], may be an effective approach, needing further exploration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Validity of AST in atypical parkinsonism remains to be established. In addition, the contribution of apraxia to poorer ADL performance in PD, as demonstrated herein and in earlier reports [6,9,10], might have consequences for occupational and physical therapy. For instance, integration of strategy training in non-demented PD, shown to be effective in apraxic stroke patients [22], may be an effective approach, needing further exploration.…”
Section: Discussionsupporting
confidence: 72%
“…IMA and LKA are frequently seen in atypical parkinsonisms, such as progressive supranuclear palsy (PSP), dementia with Lewy Bodies (DLB) and as a hallmark in corticobasal degeneration (CBD) [2]. Mild IMA may even occur in some patients with Parkinson’s disease (PD) [3,4,5,6,7] and LKA may be more common than previously thought [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that patients with PD are less efficient to perform daily hand functions. Previous studies showed fine manual dexterity deficits in buttoning, 28 coin rotation test 7 and Purdue Pegboard test 8 in individuals with PD.…”
Section: Comparison Of Jtt Score Between Healthy and Pd Subjectsmentioning
confidence: 99%
“…progressive reduction in the size of written words. 6 Standardised test such as coin rotation test, 7 and Purdue Pegboard test 8 have been used to document functional deficits in PD patients. These tests can be completed in a short time but they only evaluate the fine hand dexterity and may not be related to daily hand function.…”
Section: Introductionmentioning
confidence: 99%
“…2 Upper-limb (UL) disorders including decreased speed and amplitude of movements, 3 difficulty in performing sequential tasks, 4 and disrupted execution of fine manipulative hand activities 5,6 can restrict the lives of people living with PD and affect performance of daily tasks, 7 leisure activities, 8 and self-care. 7 The goal of physiotherapy (PT) and occupational therapy (OT) management of people with PD is to improve functional activity.…”
mentioning
confidence: 99%